Proposta de critério para avaliação de softwares de questionários eletrônicos, com base nas normas ABNT NBR ISO/IEC 9126 e 14598 - Alquimim, Hebert Bratefixe (2013)
Within the advent of Internet and its popularization, several Software that allow the creation of electronic questionnaire for a focus on evaluation of educational process in learning, appear as an alternative to the teacher, even if the course is taught in presence meeting, allowing a differentiated evaluation. This research has as aim to describe a methodology for evaluating electronic questionnaire son the Web, using as basis the standard ISO /IEC 9126, which specifies the quality of Software products and the standard ISO /IEC 14598 which describes the evaluation process of the Software product. To perform the evaluation, Webapps were identified for building electronic questionnaires that comply with the criteria established and at the end, the evaluation will have their data analyzed and compared according to the quality of Software